KONTEN VISUAL INSTAGRAM SEBAGAI MEDIA PROMOSI PADA KOMUNIKASI PEMASARAN DALAM MEMBANGUN BRAND IMAGE KAMALEENS - Rahayu Yulianti; Hasim (UKRI, 2025)
This research is motivated by the growing use of social media as a promotional tool in marketing communication, particularly through Instagram. Kamaleens, as a local fashion brand, utilizes visual content on Instagram to build a strong brand image in the minds of consumers. The purpose of this study is to identify and explain the role of visual content on Instagram @kamaleens in marketing communication to shape its brand image through three aspects of the hierarchy of effects theory: cognitive, affective, and conative. This research applies a qualitative method with a descriptive approach, while data collection techniques include in-depth interviews, observation of Instagram @kamaleens content, digital documentation, and literature study. The findings reveal that in the cognitive aspect, Kamaleens successfully builds audience awareness and knowledge of the brand through aesthetic, informative, and consistent visual design. In the affective aspect, visual content generates positive emotions through comfortable displays, relevant lifestyles, and collaborations with influencers who represent the values of the audience, thus fostering liking and preference. In the conative aspect, visual content encourages confidence and purchasing actions through persuasive messages, testimonials as social proof, and loyalty programs such as discounts and membership. Overall, the visual content strategy of Instagram @kamaleens is effective in shaping its brand image through the stages of marketing communication explained in the hierarchy of effects theory.